Inventory of the Future - Green, Julian (2001)
Escrito sobre algunas aproximaciones a París en el futuro
Keywords: GREEN, JULIAN; URBANISMO; HISTORIA; SIGLO XIX; SIGLO XX; TEORIA; FRANCIA; ÎLE-DE-FRANCE; VILLE DE PARIS; PARIS